2013
DOI: 10.1590/brag.2013.046
|View full text |Cite
|
Sign up to set email alerts
|

Eficiência de métodos de melhoramento para teor de fibra e produtividade de grãos em progênies de feijoeiro comum

Abstract: O objetivo deste estudo foi comparar métodos de melhoramento quanto à variabilidade genética e à eficiência na obtenção de progênies superiores para teor de fibra bruta e produtividade de grãos em feijoeiro comum. As progênies foram obtidas do cruzamento, em 2003, entre as linhagens carioca CNFC 7812 e CNFC 7829. A população segregante foi conduzida por bulk, bulk dentro de F2 e SSD até geração F7. Em 2008 foram amostradas aleatoriamente 64 progênies de cada método para avaliação em Goiás e Paraná. Foram obtid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 22 publications
0
10
1
1
Order By: Relevance
“…The higher estimate of broad sense heritability for BY was indicated by the black seed coat lines conducted by the bulk method (77.11%), a result similar to that reported by Jost et al (2014), indicating low environmental influence for BY. In relation to genetic variances, Silva et al (2013) evaluated common bean progenies obtained by the bulk method and found estimates of 29 769.6 and 11 591.5 kg ha -1 for BY, values superior to those found in this study, which ranged from 80.66 to 6266.34 kg ha -1 . According to Ramalho et al (2012), among the methods of conducting segregating populations, the bulk method stands out through maintaining variability among the lines selected, regardless of the generation in which sampling was carried out; the variability of the F2 generation populations was similar.…”
Section: Estimates Of Genetic Parameterscontrasting
confidence: 78%
See 2 more Smart Citations
“…The higher estimate of broad sense heritability for BY was indicated by the black seed coat lines conducted by the bulk method (77.11%), a result similar to that reported by Jost et al (2014), indicating low environmental influence for BY. In relation to genetic variances, Silva et al (2013) evaluated common bean progenies obtained by the bulk method and found estimates of 29 769.6 and 11 591.5 kg ha -1 for BY, values superior to those found in this study, which ranged from 80.66 to 6266.34 kg ha -1 . According to Ramalho et al (2012), among the methods of conducting segregating populations, the bulk method stands out through maintaining variability among the lines selected, regardless of the generation in which sampling was carried out; the variability of the F2 generation populations was similar.…”
Section: Estimates Of Genetic Parameterscontrasting
confidence: 78%
“…Rocha et al (2015) evaluated the yield of 48 carioca and black seed coat common bean progenies and reported broad sense heritability estimates ranging from 6.80% to 70.31%, results that are similar to those presented in this study. Silva et al (2013) compared lines obtained by the bulk and single seed descent (SSD) methods and found maximum values of broad sense heritability for BY of 49.8%. From the estimates of broad sense heritability presented in this study for the black seed coat lines in the bulk method and carioca seed coat lines in the genealogical method, it can be inferred that a favorable gain from selection is expected for BY.…”
Section: Estimates Of Genetic Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The selection gain was highest in the bulk method (4.45%), followed by SSD (2.97%), and bulk within F 2 (1.86%) methods (Table 3). Silva et al (2013) obtained higher genetic gains, but with the same ratio among methods. These authors worked with the same population, and evaluated the fiber content using a higher number of F 7 progenies, which were only tested at two locations.…”
Section: Methodsmentioning
confidence: 86%
“…There are some research results, such as those by Londero et al (2006) and Silva et al (2013) that provide evidence that fiber content in common beans is influenced by the environment. In this sense, it is of paramount importance to determine the magnitude of the genotype by environment interaction in the estimates of the genetic parameters related to crude fiber content so that the selection of superior lines can be more efficient.…”
Section: Introductionmentioning
confidence: 99%